If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18 + -2b = 4b + 24 Reorder the terms: -18 + -2b = 24 + 4b Solving -18 + -2b = 24 + 4b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-4b' to each side of the equation. -18 + -2b + -4b = 24 + 4b + -4b Combine like terms: -2b + -4b = -6b -18 + -6b = 24 + 4b + -4b Combine like terms: 4b + -4b = 0 -18 + -6b = 24 + 0 -18 + -6b = 24 Add '18' to each side of the equation. -18 + 18 + -6b = 24 + 18 Combine like terms: -18 + 18 = 0 0 + -6b = 24 + 18 -6b = 24 + 18 Combine like terms: 24 + 18 = 42 -6b = 42 Divide each side by '-6'. b = -7 Simplifying b = -7
| 7x^3-85x^2-79x+13=0 | | 9d^2-6d+1=0 | | 8(t-3)+4t=4(3t+4)-12 | | 11x-14=13x | | 0.25(3x-8)=2(0.5x+4) | | 6.4i+9.21=50.7 | | -4k-7+5= | | 3+1/2c=3/4c-5 | | 7-y=20 | | (8-w)(4w-2)=0 | | 10x-8=6x^2 | | 5x+35=2x+80 | | 14x=10+10 | | -(7y+2)-(6y-4)=-2 | | (x-3)/x^2 | | 16+32+x=72 | | 2x+71=4x+51 | | 4x+9y=106 | | (x+2.8)(37.2-2x)=50 | | 3x(3)-78=144 | | 6x-15=4x+13 | | (a-1)(a-5)=0 | | 8t^2-5t-25=0 | | 4n+12+n=-3n+17 | | 8.2x+1.5=21.5-1.8x | | 2t^2-6t+18=0 | | 5-8x+7=-9x-9-5 | | 2b/5-1/0=-1/2 | | x^2+30x+117=0 | | x-8.9=-4.7 | | 10b^2-18b-36=0 | | 15p+p=7-12 |